Mosquitoes Used to Draw Blood for Arbovirus Viremia Determinations in Small Vertebrates - Kading, Rebekah C. (Public Library of Science, 2014)
Serial samples from the same individuals may be required for certain virological studies, however, some small animals cannot easily be blood-sampled. Therefore, we evaluated the use of Culex quinquefasciatus Say and Aedes albopictus Skuse mosquitoes as “biological syringes” to draw blood for virus titer determinations in small vertebrates. Groups of chicks (Gallus gallus), hamsters (Mesocricetus auratus), and house sparrows (Passer domesticus) were experimentally infected with West Nile virus (WNV) or Highlands J virus (HJV). In general, good correlation was seen between mosquito- and syringe-derived blood samples at titers ≥5.0 log(10) pfu/mL serum as compared with titers <5.0 log(10) pfu/mL serum for chicks, hamsters, and sparrows. Ninety-two percent (24/26) of sparrows with virus titers >10(5) pfu/mL serum had mosquito- and syringe-derived titers within one log of each other. Sparrow viremia profiles generated from single mosquito blood meals and syringe were not significantly different (p>0.05). This technique is valuable for assessing the roles of small vertebrates in the ecologies of arboviruses, and could be used in applications beyond virology and infectious diseases, when <10 µL of whole blood is required.